DNA primer design for sex identification of Sumatran tiger body samples - IKRIMA ASRORI; DJONG HON TJONG; WILSON NOVARINO; MANSYURDIN MANSYURDIN; SYAIFULLAH SYAIFULLAH; DEWI IMELDA ROESMA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Asrori I, Tjong DH, Novarino W, Mansyurdin, Syaifullah, Roesma DI. 2023. DNA primer design for sex identification of Sumatran tiger body samples. Biodiversitas 24: 241-249. Many reports of cases of illegal trade in animal body parts have resulted in more and more samples of animal body parts being seized. Seized sample from illegal trade needs to be identified with the help of molecular methods to ensure the profile of the seized samples including the determination of their sex. At the molecular level, amelogenin gene amplifications are used to determine the sex of mammals. Previous studies using primers for amelogenin gene amplification found that amelogenin X (AMELX) and amelogenin Y (AMELY) bands in male samples were difficult to distinguish due to very small differences, 20 base pairs (bp). The difficulty of distinguishing these bands resulted in errors in detecting male and female individual samples. Therefore, it was to design a more specific primer as a way to avoid this error. The purpose of this study was to design a DNA primer for the sex identification of the Sumatran tiger (Panthera tigris sumatrae Pocock, 1929). The research was carried out using descriptive methods and molecular observation of the AMELX and AMELY Sumatran tiger sequences. The primer design results in this study were 100% able to identify the sex of the Sumatran tiger sample. The present primer design (F= 5’ TCGGTTAACAATTCCCTGGGC’3 and R= 5’AGGCCAAATAGGAGTGTGCT’3) is more specific than the primers previously reported.